The effect of whole-body vibration on subsequent sprint performance in well-trained cyclists - Rønnestad, B. R.; Slettaløkken Falch, G.; Ellefsen, S. (International Journal of Sports Physiology and Performance, 2017)
Postactivation-potentiation exercise with added whole-body vibration (WBV) has been suggested as a potential way to acutely improve sprint performance. In cycling, there are many competitions and situations where sprinting abilities are important.